Cardiac surgeons' perspectives and practices regarding people who use drugs: A scoping review. Issue 3 (6th January 2022) - Muncan, Brandon; Kim, Esther K.; Amabile, Andrea; Weimer, Melissa B.; Nguemeni Tiako, Max Jordan; Vallabhajosyula, Prashanth; Kalogeropoulos, Andreas P.; Geirsson, Arnar
Abstract: Background and Aim of Study: The rising rates of drug use and associated cardiovascular complications, particularly infective endocarditis, have led to poorer health outcomes for people who use drugs (PWUD). The objectives of this scoping review were to identify (1) attitudes of cardiac surgeons toward PWUD and (2) challenges faced in the surgical treatment of drug use‐related disease. Methods: A comprehensive literature search of three databases was performed with this assistance of a medical librarian. Articles were screened and analyzed for common themes by two independent authors. After literature review, a scoping review was conducted according to preferred reporting items for systematic reviews and meta‐analyses and Joanna Briggs Institute guidelines, summarizing existing evidence. Results: Analysis of 35 qualified articles revealed eight themes regarding the perspectives and practices of cardiac surgeons toward PWUD: (1) need for multidisciplinary care teams (45.7%); (2) insufficient resources for treatment of underlying substanceuse disorders (40.0%); (3) stigma toward PWUD (37.1%); (4) willingness of surgeons to operate (31.4%); (5) incomplete guidelines for surgical management of drug‐use related infective endocarditis (17.1%); (6) recognizing the importance of psychosocial factors (14.3%); (7) use of drug abstinence contracts (14.3%); and (8) use of stigmatizing language to describe PWUD and/or sterile injection (40.0%). Conclusions: Provision of equitable care for PWUD requires effort from multiple disciplines including cardiothoracic surgeons, infectious disease specialists, addiction medicine specialists, and social workers. Additionally, further research is needed to gather sufficient data for evidence‐based guidelines in the treatment of cardiac complications in PWUD.